Tumour devascularisation as a potential immunotherapeutic strategy - Buchler, Tomas; Vasek, Pavel; Spisek, Radek; Skrobanek, Pavel; Horejsi, Vaclav (Oncoimmunology, 2019)
Complete tumour devascularisation (CTD) is a surgical technique which entails the complete disruption by ligation or cutting of afferent and efferent tumour vasculature which remains in situ. In some animal models, CTD induces immune responses that lead to regression of distant metastases and protective immunity.
Keywords: cancer; Immunotherapy; tumour ligation; devascularisation; ischaemia